Evaluation of Pharmaceutical Quality of Mesalamine Delayed Release Tablets Using a New High Sensitivity Reversed-Phase UPLC Method for its Genotoxic/Aniline Impurity - Rakshit Kanubhai Trivedi; Mukesh C. Patel (E-Journal of Chemistry)
A reversed phase ultra performance liquid chromatography (UPLC) method was developed and validated for the quantification of aniline in mesalamine delayed-release tablets. The optimization of the experimental condition was carried out considering some important requirements like, detection limit, short run time and reproducibility. In the present study, isocratic reversed-phase UPLC method was developed for determination and separation of aniline from the drug product. The drug and impurity are well separated by using a reversed phase (Reprosil Gold C18-XBD) column and mobile phase comprising of buffer pH 6.0 and acetonitrile in the ratio of 90:10 v/v. Other UPLC parameters which were optimised are flow rate, 0.5 mL/min; detection wavelength, 200 nm; column oven temperature, 50 °C and injection volume 7 µL. Stability indicating capability was also established by forced degradation experiments. The method was validated as per ICH guideline. LOQ (limit of quantification) concentration (18 ng/mL) was found precise with RSD of less than 2%. In essence, the present study provides an improved low detection limit and lower run time for evaluation of pharmaceutical quality of mesalamine delayed-release formulation. Moreover, the developed method was also successfully applied for quantification of aniline in mesalamine delayed-release formulation. The same method can also be used for determination of aniline from drug substances.